Financial Analysis Of Citrus “Keprok 55” In Coventional Way and Using Sprinkler Irrigation - Bambang Suharto; Liliyan Dewi Susanawati (Research Journal of Life Science, 2016)
Batu-Malang Government area is one of central production of citrus ”Keprok 55” in East Java. In dry season, citrus produce low production level, because there is unsufficient water inside the soil. Based on this facts, some efforts is needed in order to increase the citrus production especially to face the dry season, through sprinkle irrigation system to increase citrus production. Sprinkle irrigation system has been installed on citrus plantation in Selorejo Village, Batu.Citrus is one of the horticultural commodities which have priority to be developed. One type of citrus that favored consumers are mandarin (tangerine). During the period 2005-2009 tangerine imports reached 504,063 tonnes, or about 100,813 tonnes per year with a value of US $ 80,569,300. Management of commodity Citrus 55 in Selorejo village, subdistrict Dau, Malang not get maximum benefit due to the limitations of the use of technological innovation as well as the lack of capital. The experiment calculated HPP, BEP, NPV, R/C ratio, IRR and PP. This study was to compare the effect of management changes Citrus 55 between conventional and sprinkler irrigation. The financial viability of commodity management Citrus 55 in Selorejo Village declared eligible to run either conventionally or with sprinkler irrigation. Age commodity management business is ten years. Conventional management NVP value is IDR 1,234,468,408 and the value of NVP management with the use of sprinkler irrigation is IDR 5,200,599,957. PP value of conventional management is 5 years 2 months and sprinkler irrigation is 2 years and 5 months. Conventional management IRR value is 59.47% and value of management use sprinkle is 68.08%. R/C Ratio with conventional management is 1.4 and value R/C Ratio with sprinkle is 5.7. BEP value with management conventional is 5,719 kilograms and with sprinkle is 16,059 Kilograms. HPP value with management conventional is IDR 784 and with sprinkle is IDR 191.